Children’s Information-Related Internet Use at Home: The Role of the Quantity and Quality of Parental Support and Children’s Motivation - Gruchel, Nicole; Kurock, Ricarda; Bonanati, Sabrina; Buhl, Heike M. (Journal of Research in Childhood Education)
Children’s information-related internet use positively affects their acquisition of computer- and information-related skills. Nevertheless, this use still occurs predominantly in the family context. Parents’ support of their children’s internet use can motivate them to use the internet for information-related purposes. However, while parents’ support seems to be important, the quantity and quality of parental support have been shown to have different associations with children’s motivation. Thus, the goal of the current study was to examine the relationship between parents’ support (quantity and quality), children’s motivation to engage in information-related internet use, and children’s actual information-related internet use (practical and school- or learning-related use) using structural equation modeling. In addition, we examined the mediating effects of children’s motivation. Specifically, 492 12-year-old German children answered a paper-and-pencil questionnaire. We found positive associations between the quantity and quality of parents’ support and children’s intrinsic and extrinsic motivation, while only structure-giving support was found to be related to children’s intrinsic motivation. The quantity of support was directly related to children’s school- or learning-related use, while intrinsic motivation was associated with both forms of information-related internet use. Furthermore, we confirmed that children’s motivation is an important mediator in this context. The implications of these findings for parents and children are considered.
Keywords: children's motivation; information-related internet use; quality of parental support; quantity of parental support

Conceptualizing smart service systems - Beverungen, Daniel; Müller, Oliver; Matzner, Martin; Mendling, Jan; vom Brocke, Jan (Electronic Markets)
Recent years have seen the emergence of physical products that are digitally networked with other products and with information systems to enable complex business scenarios in manufacturing, mobility, or healthcare. These “smart products”, which enable the co-creation of “smart service” that is based on monitoring, optimization, remote control, and autonomous adaptation of products, profoundly transform service systems into what we call “smart service systems”. In a multi-method study that includes conceptual research and qualitative data from in-depth interviews, we conceptualize “smart service” and “smart service systems” based on using smart products as boundary objects that integrate service consumers’ and service providers’ resources and activities. Smart products allow both actors to retrieve and to analyze aggregated field evidence and to adapt service systems based on contextual data. We discuss the implications that the introduction of smart service systems have for foundational concepts of service science and conclude that smart service systems are characterized by technology-mediated, continuous, and routinized interactions.
Keywords: Boundary object; Internet of things; Service science; Smart products; Smart service

Internet of Things Architecture for Handling Stream Air Pollution Data - Kersting, Joschka; Geierhos, Michaela; Jung, Hanmin; Kim, Taehong (Proceedings of the 2nd International Conference on Internet of Things, Big Data and Security)
In this paper, we present an IoT architecture which handles stream sensor data of air pollution. Particle pollution is known as a serious threat to human health. Along with developments in the use of wireless sensors and the IoT, we propose an architecture that flexibly measures and processes stream data collected in real-time by movable and low-cost IoT sensors. Thus, it enables a wide-spread network of wireless sensors that can follow changes in human behavior. Apart from stating reasons for the need of such a development and its requirements, we provide a conceptual design as well as a technological design of such an architecture. The technological design consists of Kaa and Apache Storm which can collect air pollution information in real-time and solve various problems to process data such as missing data and synchronization. This enables us to add a simulation in which we provide issues that might come up when having our architecture in use. Together with these issues, we state r easons for choosing specific modules among candidates. Our architecture combines wireless sensors with the Kaa IoT framework, an Apache Kafka pipeline and an Apache Storm Data Stream Management System among others. We even provide open-government data sets that are freely available.
Keywords: Wireless Sensor Network; Internet of Things; Stream Data; Air Pollution; DSMS; Real-time Data Processing

Fans: Entscheider oder Supporter? Eine organisationssoziologische Analyse zur Mitbestimmung in Fußballclubs - Riedl, Lars; Giesselmann, Marco (Sozialwissenschaftliche Perspektiven der Fußballfanforschung)
Keywords: Befragung; Demokratie; Entscheidung; Entscheidungsprozess; Fan; Fußballspiel; Gruppe; soziale; Internet; Interview; Kommunikation; Organisationssoziologie; Sozialwissenschaft; Sportsoziologie; Sportverein; Untersuchung; empirische Vereinsführung

Internet im Kalten Krieg: eine Vorgeschichte des globalen Kommunikationsnetzes - Schmitt, Martin
Keywords: Ost-West-Konflikt; Hochschulschrift; Internet; Geschichte; Netzwerk; Geschichte 1967-1975; Technikgeschichte; Computernetzwerk

Measuring eTrust in distributed systems - General Concept and Application to Internet Voting - Volkamer, Melanie; Schryen, Guido (Proceedings of the 23rd Bled eConference)
Emerging digital environments and infrastructures, such as distributed services and computing services, have generated new options of communication, information sharing, and resource utilization in past years. Different distributed trust concepts are applied to increase trust in such systems. However, these concepts yield to rather complex architectures which make it difficult to determine which component or system needs to be trusted. This paper presents a novel trust measurement method for distributed systems which enables the t identification of weak points in the overall system architecture. The measurement method includes the specification of a formal trust language and its representation by means of propositional logic formulas. The applicability of the proposed concepts is demonstrated by conducting a case study on the Internet voting system that was used in the 2007 parliamentary elections in Estonia.
Keywords: distributed trust concepts; measuring etrust; Internet voting

Security in Large-Scale Internet Elections: A Retrospective Analysis of Elections in Estonia, The Netherlands, and Switzerland - Schryen, Guido; Rich, Eliot (IEEE Transactions on Information Forensics & Security)
Remote voting through the Internet provides convenience and access to the electorate. At the same time, the security concerns facing any distributed application are magnified when the task is so crucial to democratic society. In addition, some of the electoral process loses transparency when it is encapsulated in information technology. In this paper, we examine the public record of three recent elections that used Internet voting. Our specific goal is to identify any potential flaws that security experts would recognize, but may have not been identified in the rush to implement technology. To do this, we present a multiple exploratory case study, looking at elections conducted between 2006 and 2007 in Estonia, Netherlands, and Switzerland. These elections were selected as particularly interesting and accessible, and each presents its own technical and security challenges. The electoral environment, technical design and process for each election are described, including reconstruction of details which are implied but not specified within the source material. We found that all three elections warrant significant concern about voter security, verifiability, and transparency. Usability, our fourth area of focus, seems to have been well-addressed in these elections. While our analysis is based on public documents and previously published reports, and therefore lacking access to any confidential materials held by electoral officials, this comparative analysis provides interesting insight and consistent questions across all these cases. Effective review of Internet voting requires an aggressive stance towards identifying potential security and operational flaws, and we encourage the use of third party reviews with critical technology skills during design, programming, and voting to reduce the changes of failure or fraud that would undermine public confidence.
Keywords: e-voting; Internet voting; Internet election; security; verifiability; RIES; Estonia; Neuchâtel

Practical Security of Large-scale Elections: An Exploratory Case Study of Internet Voting in Estonia - Schryen, Guido (7th Workshop on e-Business (WEB 2008, AIS Special Interest Group on E-Business))
The Estonian parliamentary election in 2007 is regarded as a success story of large-scale Internet elections. I use this election in a single case study on practical security to show that low quality of security and its management does not necessarily prevent large-scale Internet elections from being conducted. I also provide research propositions with regard to future challenges for large-scale Internet elections.
Keywords: Internet voting; large-scale election; Estonian parliamen- tary election; security; security management

A Novel Uncertainty Decoding Rule With Applications to Transmission Error Robust Speech Recognition - Ion, Valentin; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In this paper, we derive an uncertainty decoding rule for automatic speech recognition (ASR), which accounts for both corrupted observations and inter-frame correlation. The conditional independence assumption, prevalent in hidden Markov model-based ASR, is relaxed to obtain a clean speech posterior that is conditioned on the complete observed feature vector sequence. This is a more informative posterior than one conditioned only on the current observation. The novel decoding is used to obtain a transmission-error robust remote ASR system, where the speech capturing unit is connected to the decoder via an error-prone communication network. We show how the clean speech posterior can be computed for communication links being characterized by either bit errors or packet loss. Recognition results are presented for both distributed and network speech recognition, where in the latter case common voice-over-IP codecs are employed.
Keywords: automatic speech recognition; bit errors; codecs; communication links; corrupted observations; decoding; distributed speech recognition; error-prone communication network; feature vector sequence; hidden Markov model-based ASR; hidden Markov models; inter-frame correlation; Internet telephony; network speech recognition; packet loss; speech posterior; speech recognition; transmission error robust speech recognition; uncertainty decoding; voice-over-IP codecs

Preventing E-mail Spam: The Conceptualization and the Analysis of an Infrastructure Framework - Schryen, Guido
Spamming remains a form of Internet abuse, which burdens the Internet infrastructure, is generally regarded as an annoyance, and is said to cause a huge economic harm. Many technological, organizational, and legislative anti-spam measures have already been proposed and implemented, but have not led to any substantial decrease in the number of spam e-mails. We propose a scalable and flexible infrastructure framework that integrates several anti-spam measures and that features both a technological and an organizational facet. The key element of our infrastructure is a new organizational unit that reliably and transparently limits the number of e-mails that can be sent per day and per account. We also analyze the proposed framework in terms of its theoretical effectiveness, the required resources, and its limitations.
Keywords: Email; Infrastructure; Internet; Spam

E-Democracy: Internet Voting - Schryen, Guido (Proceedings of the IADIS International Conference WWW Internet 2003. vol. 2)
Voting via the Internet is part of electronic government and electronic democracy. However, there are many obstacles which have to be overcome, especially legal restrictions have to be transformed into technical and security solutions. In the first part the article discusses advantages and disadvantages of Internet elections, shows different application fields, and presents important international pilot schemes (political and business ones). in the second part, due to democratic basic principles, technological security aspects are worked out.
Keywords: Internet Voting; Online polls; E-Democracy; Security

Internet-Wahlen - Schryen, Guido (6. Internationale Tagung Wirtschaftsinformatik)
Zusammenfassung: Im Rahmen des E-Governments werden zunehmend Internetwahlen diskutiert. Der Beitrag diskutiert zunächst die Vor- und Nachteile derartiger Wahlen und zeigt Anwendungsgebiete sowie durchgeführte Pilotprojekte im politischen wie auch wirtschaftlichen Bereich auf. Im Rahmen eines Anforderungssystems werden anschließend aus demokratischen Wahlgrundsätzen sicherheitstechnologische Anforderungen herausgearbeitet. Zu deren Adressierung werden kryptographischen Wahlkonzepte herangezogen, von denen die wichtigsten vorgestellt werden. Aufgrund der Komplexität der Anforderungslandschaft wird ein sicherheitstechnologisches Strukturmodell vorgestellt, das insbesondere dazu dient, die Sicherheit(skomponenten) eines Wahlsystems systematisch mit den Anforderungen abzugleichen. Der Artikel schließt mit einem Ausblick auf notwendige Untersuchungen.
Keywords: Internet-Wahlen; E-Democracy; Sicherheit; Kryptographie

Innovative Concepts for Configurating Shared Workspaces through Visual Programming - Dücker, M.; Müller, Wolfgang; Rubart, Jessica (Proceedings of the 32nd Annual Hawaii International Conference on Systems Sciences)
CSCW systems like BSCW (Basic Support for Cooperative Work), HyperNews, and Lotus Notes have been successfully introduced to support the cooperation of geographically distributed work groups. Unfortunately, some of these software systems are not flexible enough to be customized easily to the requirements of an individual user. Most of the environments can only be configured by experts through complex programming. In this article we introduce VIP space, a shared workspace space in the sense of exchanging and processing shared objects between members of distributed work groups. VIP space can be easily adapted to the user's individual views and needs by means of a visual programming language. In VIP space, objects of the shared workspace are moved by drag and drop between task fields. Task fields are programmed by visual "if-then" rules applying a combination of icon- and form-based techniques. When a document represented by an icon is dropped on a task field its rules are checked and actions of the selected rules are excited. VIP space is finally demonstrated in an Internet course application.
Keywords: Application software; Electronic mail; Computer networks; Collaborative work; Teleconferencing; Asynchronous communication; Software systems; Internet; Computer applications; Discussion forums